Effect of oxidizing agents on the treatment of a Colombian lead ore by alternative hydrometallurgical processes - Borda J.; Salamanca I.D.; Torres R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The metallurgy of lead presents significant environmental and public health challenges due to its toxicity. This is why it has been necessary to develop hydrometallurgical processes as alternatives for obtaining metal with a more sustainable and environmentally safe approach. However, these processes may involve complex chemical reactions and the use of specific chemical reagents, which may require rigorous control and monitoring to ensure the efficiency of the process and the safety of the personnel involved. In this research, the recovery of lead from a Colombian mineral with low metal content was studied by hydrometallurgical processes in carboxylic media under ambient conditions. A preliminary chemical treatment was necessary to improve the metal extraction. For this purpose, two hydrometallurgical treatments were used: i) pneumatic agitation with ozone injection and ii) mechanical agitation with hydrogen peroxide dosing. The lead extractions from the pretreated ore were similar to those from the leach without pretreatment. This situation attributed the dissolution of the lead to the complexing effect of the carboxylic agent rather than to the effect of the pretreatments. The direct addition of peroxide to the citrate leach resulted in an extraction of 50% of the metal, an improvement of more than 30% over the leach without the addition of the oxidizing agent. The leaching of the ore with 0.5M citrate and pH 4.5 yielded a redox potential of 926 mV, which ensured the high activity of the electrons in the chemical reaction and therefore the lead ions dissolution.